2020
DOI: 10.7759/cureus.7098
|View full text |Cite
|
Sign up to set email alerts
|

Rosuvastatin Use Implicated in the Drug Reaction with Eosinophilia and Systemic Symptoms

Abstract: Drug reaction with eosinophilia and systemic symptoms (DRESS) is a life-threatening druginduced hypersensitivity reaction that is most closely associated with antiepileptics and antibiotics. While cases of DRESS are rare, here we present a case of DRESS in an adult male following administration of rosuvastatin who presented with fevers, generalized rash, and facial fullness. Vitals on presentation were temperature 102 o F, pulse 95/min, blood pressure 95/47 mmHg, and respiratory rate of 14/min. His physical ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“… 45 As such, reports of negative HHV-6 assessed only once immediately or shortly after DRESS onset may have missed later reactivation. 8 , 11 , 44 , 46 - 50 While there are many reports of delayed seroconversion or reactivation, 9 , 15 , 33 , 37 , 51 - 54 sometimes with initially undetectable viral loads, 21 , 27 , 55 , 56 HHV-6 reactivation at the onset of DRESS is possible, as well. 8 , 28 , 32 , 57 , 58 It should be noted that HHV-6 reactivation has not been reported before DRESS onset, which suggests that HHV-6 reactivation likely does not cause DRESS.…”
Section: Resultsmentioning
confidence: 99%
“… 45 As such, reports of negative HHV-6 assessed only once immediately or shortly after DRESS onset may have missed later reactivation. 8 , 11 , 44 , 46 - 50 While there are many reports of delayed seroconversion or reactivation, 9 , 15 , 33 , 37 , 51 - 54 sometimes with initially undetectable viral loads, 21 , 27 , 55 , 56 HHV-6 reactivation at the onset of DRESS is possible, as well. 8 , 28 , 32 , 57 , 58 It should be noted that HHV-6 reactivation has not been reported before DRESS onset, which suggests that HHV-6 reactivation likely does not cause DRESS.…”
Section: Resultsmentioning
confidence: 99%
“…DRESS is an individual form of severe hypersensitivity reaction characterized not only by the presence of widespread skin inflammation but also by fever and abnormal hematological findings with multiorgan involvement. Commonly DRESS is associated viral reactivation including the human herpes virus family (HHV-6 and 7), Epstein–Barr virus (EBV), cytomegalovirus (CMV), and varicella zoster, which worsen the syndrome leading to poor prognosis. As in seen with SJS/TEN, anticonvulsants and antibiotics are common therapeutic families associated with the disease, although more than 44 drugs have been associated with DRESS . Oddly, although DRESS is labeled as a severe cutaneous drug reaction, in some rare cases, skin damage is not seen …”
Section: Clinical Manifestations Of Drug Hypersensitivity Reactionsmentioning
confidence: 99%
“…It is not surprising to see these overlapping features between severe cutaneous reactions, because as in SJS/TEN the number of infiltrating CD8 + cells is higher than CD4 + cells at the site of the skin reaction, and the presence of IL-17 secreting cells has been reported . Detailed sequencing studies have shown an oligoclonal response in CD8 + T-cells, and the increase of specific public TCR clones has not been reported .…”
Section: Clinical Manifestations Of Drug Hypersensitivity Reactionsmentioning
confidence: 99%
“…Many different medications are implicated in DRESS, however the most common causes are typically seen with anticonvulsants and antibiotics [1,4]. Statin class medications are not typically implicated or associated with DRESS [1].…”
Section: Allergy Asthma and Clinical Immunologymentioning
confidence: 99%
“…Drug reaction with eosinophilia and systemic symptoms (DRESS) is a serious, potentially life threatening condition that typically presents with generalized skin rash, fevers, enlarged lymph nodes, hematological abnormalities in addition to eosinophilia and multiorgan dysfunction [1]. The diagnosis of DRESS is often challenging, with heterogeneity in clinical presentation, often initially misdiagnosed as infection [2].…”
Section: Introductionmentioning
confidence: 99%